(untitled) (Communications in Computational Chemistry, 2018)
The energy barrier of excited state proton transfer (ESPT) process in 3-hydroxyflavone (3HF) was studied considering the solvent effects. It was found that the ESPT energy barrier increased with the increase of solvent polarity. But the ESPT energy barrier of 3HF in methanol is lower than in vacuum, n-hexane and acetonitrile. It was found that methanol molecule lowers the ESPT energy barrier by forming a seven-membered-ring 3HF-methanol complex.